Digital Promotion Strategy and Consumer Purchasing Decisions on TikTok Shop - Sunarjo, Wenti Ayu; Nurhayati, Siti; Sabana, Choliq (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2026)
The rapid growth of social commerce has transformed consumer purchasing behavior in the online fashion industry. TikTok Shop, which integrates social media and e-commerce features, has become an effective marketing platform for local fashion brands, including Jiniso. This study aims to examine the effects of flash sales, free shipping, and content marketing on consumer purchase decisions for Jiniso products through TikTok Shop. A quantitative approach was employed using survey data collected from 97 consumers who had previously purchased Jiniso products via TikTok Shop. Multiple linear regression was utilized to analyze the data. The results reveal that flash sales significantly influence purchase decisions. Free shipping also exerts a positive and significant effect on purchase decisions. Furthermore, content marketing emerged as the strongest predictor of consumer purchase decisions. Simultaneously, all three variables significantly affect purchase decisions. These findings indicate that successful marketing in social commerce environments is not solely driven by price promotions but also by the ability to create engaging and informative content that strengthens consumer involvement. This study provides practical implications for local fashion businesses in optimizing digital marketing strategies to enhance competitiveness in the digital economy era.